2021
DOI: 10.1080/21645515.2021.1935172
|View full text |Cite
|
Sign up to set email alerts
|

The pivotal roles of the host immune response in the fine-tuning the infection and the development of the vaccines for SARS-CoV-2

Abstract: SARS-CoV2 infection induces various degrees of infections ranging from asymptomatic to severe cases and death. Virus/host interplay contributes substantially to these outcomes. This highlights the potential roles of the host immune system in fighting virus infections. SARS-CoV-2. We highlighted the potential roles of host immune response in the modulation of the outcomes of SARS-CoV infections. The newly emerged SARS-CoV-2 mutants complicated the control and mitigation strategies measures. We are highlighting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 122 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…Evaluating the durability of the immune response induced by the SARS-CoV-2 infection, particularly the humoral immune response, is critical for understanding the pathogenesis of SARS-CoV-2 and evaluating the protection efficiency of the current vaccines. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating the durability of the immune response induced by the SARS-CoV-2 infection, particularly the humoral immune response, is critical for understanding the pathogenesis of SARS-CoV-2 and evaluating the protection efficiency of the current vaccines. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the durability of the immune response induced by the SARS-CoV-2 infection, particularly the humoral immune response, is critical for understanding the pathogenesis of SARS-CoV-2 and evaluating the protection efficiency of the current vaccines. 2,3 Human antibody responses against SARS-CoV-2 4 are generated by viral proteins such as spike glycoprotein (S protein) and nucleocapsid protein, of which the former can induce neutralizing antibodies required for viral neutralization and eradication by inhibiting viral interaction with the host cells. 5 SARS-CoV-2 penetrates host cells similarly to SARS-CoV-1 by binding to angiotensin-converting enzyme 2 (ACE2) using the S protein.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, after crossing the mucosal barrier, viral particles bind to host cells through the interaction of the viral spike protein with the receptor ACE-2, facilitated by the co-receptor transmembrane protease serine 2 (TMPRSS2). Following this interaction, the virus fuses with the cellular membrane and releases its genomic RNA into the cytoplasm of the cells during viral replication [ 81 , 82 ] ( Figure 1 ). Furthermore, endosomal TLR-3 receptors can identify dsRNA during SARS-CoV-2 replication, and this induces the activation of the transcription factors and the associated signaling pathways, including interferon-regulatory factors and nuclear factor-kappa B (NF-κB), which results in the activation of type I IFNs, as well as proinflammatory cytokines, and the expression of type I IFN can induce an antiviral state in uninfected cells [ 83 ].…”
Section: The Role Of Mucosal Immunity During Sars-cov-2 Infectionmentioning
confidence: 99%
“…Experience with the SARS-CoV-2 vaccination programmes showed that protective immunity gained by natural infection with SARS-CoV-2 is poor compared to the much higher levels of virus-neutralizing antibodies and T cells induced by the vaccines [101,102]. An emerging problem is the development of new variants of SARS-CoV-2 with the ability to escape natural and vaccine-induced immunity [103,104]. This fact prompts the need for updated vaccines [105], and confirms that a global vaccination program with high efficacy vaccines is one of the most important challenges of the next years.…”
Section: Reinfection With Sars-cov-2-when Does It Occur and How Can It Be Verified?mentioning
confidence: 99%